2014, No. 16, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Current issues on audit and control Aurelija Kustienė, Independent audit as a strategic tool to reduce the information asymmetry on the market, 10 Rasa Kanapickienė, Control measures in the accounting of intangible assets of public sector entities, 19 Daiva Tamulevičienė, The concept of controlling and its evolution, 28 Rūta Klimaitienė, Kristina Rudžionienė, Andželika Verbliugevičiūtė, The effectiveness of ABC method in small companies, 40 Financial analysis and evaluation Jonas Mackevičius, Lukas Giriūnas, Model of evaluation of enterprise risk management, 55 Jovita Jusytė, Irma Kamarauskienė, Public sector entities in the financial statements relative analysis: theoretical and practical aspects, 64 Gintarė Labonaitė, Rasa Subačienė, Methodology for net profitability analysis, 79 Lukas Giriūnas, Gintarė Giriūnienė, Research on entrepreneur identification, 89 Gintarė Giriūnienė, Research on entrepreneurship indicators, 97 Solutions in financial science Erika Beniušytė, Aurelija Zonienė, Financial model of investments to fixed assets, 105 Deimena Kiyak, Individual investor investment alternatives assessment criteria modelling, 114 Jonas Mackevičius, Vilius Savickas, Prof. Vladas Jurgutis on banks: his insights and their development in works Lithuanian author‘s, 129 Challenges in preparing specialists of accounting and finance Romualdas Valkauskas, Assessment competences professionals, 141 Liucija Budrienė, Milda Kvekšienė, Audronė Meškelienė, Challenges and trends of recognition of accountants’ competences, 149 Audronė Bagdonienė, Fausta Smolenskienė, Analysis of the accounting speciality collage graduates’ employment opportunities at the labour market in the context of the workforce supply and demand, 160 Lina Kušleikienė, Renata Šivickienė, Usage of methods, which develop skills of entrepreneurship, during financial field lectures at Siauliai State College, 172